On the origin of sperm epigenetic heterogeneity. Issue 5 (May 2016) - Laurentino, Sandra; Borgmann, Jennifer; Gromoll, Jörg
Abstract: The influence of epigenetic modifications on reproduction and on the function of male germ cells has been thoroughly demonstrated. In particular, aberrant DNA methylation levels in sperm have been associated with abnormal sperm parameters, lower fertilization rates and impaired embryo development. Recent reports have indicated that human sperm might be epigenetically heterogeneous and that abnormal DNA methylation levels found in the sperm of infertile men could be due to the presence of sperm populations with different epigenetic quality. However, the origin and the contribution of different germ cell types to this suspected heterogeneity remain unclear. In this review, we focus on sperm epigenetics at the DNA methylation level and its importance in reproduction. We take into account the latest developments and hypotheses concerning the functional significance of epigenetic heterogeneity coming from the field of stem cell and cancer biology and discuss the potential importance and consequences of sperm epigenetic heterogeneity for reproduction, male (in)fertility and assisted reproductive technologies (ART). Based on the current information, we propose a model in which spermatogonial stem cell variability, either intrinsic or due to external factors (such as endocrine action and environmental stimuli), can lead to epigenetic sperm heterogeneity, sperm epimutations and male infertility. The elucidation of the precise causes for epimutations, the conception of adequate therapeutic options and the development of sperm selection technologies based on epigenetic quality should be regarded as crucial to the improvement of ART outcome in the near future.